Brendan meets Columbus: A more commodious islescape. Issue 4 (December 2016) - Smith, James
Abstract This paper proposes that we can reimagine insular literatures and medieval islescapes as commodious seas of cultural and intellectual loci that span time, culture, and text alike. By moving beyond the rhetoric of insular separation or connectivity, we can see that islands connect even when medieval minds saw separation. The essay focuses on the Brendan legend and the commodious cultural 'sea of islands' that it inhabits, a space that connects the modern reader to a history of other connections, fact to fancy, and the real and the imaginary. When sailing in this sea, Brendan meets Columbus, and the late medieval idea of a lost island spreads though space and time.